Evaluation of Locomotor and Morpho-histological Effect for Platelet Rich Plasma and Silver Nanoparticles on Healing Process of Achilles Tendon (Comparative Experimental Study in Rabbits) - Elrashidy, Mohamed H.; Salama, Mohamed M.A.; Abedellaah, Bahaa Eldeen A.; Ali, Fatma Abo Zakaib; El-Hawari, Sayed F. (Journal of Advanced Veterinary Research, 2023)
Tissue engineering is a new treatment option provided encouraging results in orthopedic surgery. In the present study, we compare between platelet rich plasma (PRP) and silver nanoparticles (AgNPs) in the healing process of achilles tendon. This comparison depending upon the evaluation of locomotor and morpho-histological parameters for each treatment. The current study was carried out on 45 apparently healthy adult female rabbits. Locomotor evaluation was done through numerical score at intervals of 2, 4, 6 and 8 weeks postoperatively. Morpho-histological evaluation was performed through numerical score at intervals of 2, 3 and 6 weeks postoperatively. Results of the current study revealed that PRP and AgNPs were better than control group regarding to lameness, pain on complete flexion of tarsal joint, adhesion of tendon to the skin and signs of inflammation. However, PRP is better than both control and AgNPs groups in decreasing lameness and adhesion of tendon to the skin. Morpho-histological examination revealed that PRP is better than both control and AgNPs in improving color of the tendon. PRP and AgNPs were better than control group concerning collagen maturation, fibroblast number, angiogenesis, and surgical gap reduction. However, PRP is better than both control and AgNPs in decreasing signs of inflammation and increasing collagen maturation. We concluded that using PRP for treatment of ruptured achilles tendon provides better prognosis than AgNPs treatment.Â 